DISINFECTION AND STERILIZATION IN OUTPATIENT OCCUPATIONAL HEALTH SERVICES - Aline Mara Jacoby; Karen Cristina Jung Rech; Rosana Amora Ascari (Universidade Federal do Paraná, 2016)
This study aimed to investigate the process of disinfection and sterilization of materials in outpatient occupational health units, in the Brazilian states of Santa Catarina, Rio Grande do Sul, and Mato Grosso do Sul. It is a case study undertaken in 15 outpatient occupational health units, in June - September 2013, with a questionnaire applied individually to the professionals working in the area of sterilization in the company's head office.All the units use the autoclave as the method of sterilization, undertaken in the medical-dental procedure rooms. The following were identified: there is a lack of standardization of products' labeling, validation tests and records of the sterilizations undertaken. The quality and safety of the sterilization process are compromised in the units studied, and require intervention in the physical structure and redefinition of the processes of monitoring and recording the sterilizations for improvement of the health conditions, and of the worker's safety.